The Influence of Green Banking, Credit Risk, and Operational Efficiency on The Financial Performance of Conventional Banks in 2020-2023 - Firdausi Nurnuzula Afandi; Puji Endah Purnamasari (Golden Ratio of Auditing Research, 2026)
This research endeavor is directed toward assessing the impact of Green Banking, Credit Risk, and Operational Efficiency on the Financial Performance of conventional banks in Indonesia in 2020-2023. Green banking was evaluated through the Green Banking Disclosure Index (GBDI), credit risk was represented by the Non-Performing Loan (NPL) ratio, the BOPO ratio indicated operational efficiency, and financial performance was assessed using Return on Assets (ROA). This research adopts a quantitative methodology utilizing pre-existing datasets derived from the annual financial statements of banks listed in collaboration with the Financial Services Regulatory Authority (OJK). The analysis employed panel data regression models executed via EViews software. Empirical findings reveal that green banking exerts a marginally significant influence on financial performance, whereas credit risk does not demonstrate a statistically meaningful relationship. Conversely, operational efficiency exhibits a significant inverse association with financial performance. The independent variables account for 73% of the heterogeneity observed in financial performance, as represented by the recalibrated coefficient of determination. These outcomes underscore the critical role of enhancing cost-efficiency strategies and advancing environmental banking initiatives to foster long-term financial sustainability within the banking sector.